The Policies of Pakistani Government and United Nations in Empowering Women on Educational Aspect - Sri Intan Meutia (2013)
In Pakistan, particularly in rural and sub-urban areas, women are situated largely at the bottom end of the educational system in comparison to their male counterparts. Traditionally it is assumed that women are limited to their homes and men are the breadwinners of the family. Pakistan has not been able to bring children especially girls to school. Low enrollment rate and rapid population growth have led to steady increase in out of school children especially girls, and resultantly number of il